An analysis of body proportions in children with CHARGE syndrome using photogrammetric anthropometry. Issue 8 (27th May 2019) - Penders, Bas; Dijk, Dieuwerke R.; Bocca, Gianni; Zimmermann, Luc J. I.; van Ravenswaaij‐Arts, Conny M. A.; Gerver, Willem‐Jan M.
Abstract: Background: Growth retardation is one of the main hallmarks of CHARGE syndrome (CS), yet little is known about the body proportions of these children. Knowledge of body proportions in CS may contribute to a better characterization of this syndrome. This knowledge is important when considering starting growth‐stimulating therapy. Methods: For this cross‐sectional study, we selected 32 children with CS and a CHD7 mutation at the Dutch CHARGE Family Day in 2016 or 2017 and the International CHARGE conference in Orlando, Florida, in 2017. We used photogrammetric anthropometry—a measurement method based on digital photographs—to determine various body proportions. We compared these to measurements in 21 normally proportioned children with growth hormone deficiency, using independent‐samples t test, Mann–Whitney U test, or chi‐square test as appropriate. Results: Children with CS appear to have a shorter trunk in proportion to their height, head length, and arm length. Children with CS also had smaller feet proportional to tibia length compared to controls. The change of body proportions with age was similar in children with CS and controls. Conclusion: Body proportions in children with CS are significantly different from those of normally proportioned controls, but a similar change of body proportions with age was noted for both groups.